PERCEPTION OF PHYSICS TEACHERS AND STUDENTS ABOUT E-MODULES USING STEM-INTEGRATED FLIPPED CLASROOM APPROACH TO IMPROVE CRITICAL THINKING SKILLS - Puspitasari, Reni Dwi; Herlina, Kartini; Suyatna, Agus (Jurnal Pembelajaran Fisika, 2020)
PERCEPTION OF PHYSICS  TEACHERS AND STUDENTS ABOUT E-MODULES USING STEM-INTEGRATED  FLIPPED CLASROOM APPROACH TO IMPROVE CRITICAL THINKING SKILLS  Reni.DPS1, Kartini.H2, Agus.Suyatna31Physics  Education of  Graduate Program, Lampung  University2Physics  Education of  Graduate Program, Lampung  University3Physics  Education of  Graduate Program, Lampung  University Jl. Sumantri Brojonegoro No. 01, Lampung,  Indonesia.Correspondence author: renidps53@gmail.com Abstract: The purpose of this study was  to describe the perceptions of teachers and students related to the use of e-modules using the integrated STEM flipped classroom approach. The approach used was STEM-integrated flipped classroom . Data collection methods using a questionnaire were analyzed with descriptive analysis with the 15 professional and unprofessional teachers and 30 students in Lampung province as respondents . The results of teachers 'perceptions about e-modules amounted to 66.7% if presented as belonging to the required category, while the results of students' perceptions using e-modules amounted to 63.3% and  classified as needed. Practice was also needed in making e-modules with the results of 73.3% of teachers answering practical answers and 56.7% of students answering practical questions. It can be inferred that students need new teaching materials to support practical and easy to use learning t any time limit